2022
DOI: 10.3390/cells11233892
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stromal/Stem Cell-Derived Extracellular Vesicles Promote Corneal Wound Repair by Regulating Inflammation and Angiogenesis

Abstract: Severe corneal damage leads to complete vision loss, thereby affecting life quality and impinging heavily on the healthcare system. Current clinical approaches to manage corneal wounds suffer from severe drawbacks, thus requiring the development of alternative strategies. Of late, mesenchymal stromal/stem cell (MSC)-derived extracellular vesicles (EVs) have become a promising tool in the ophthalmic field. In the present study, we topically delivered bone-marrow-derived MSC-EVs (BMSC-EVs), embedded in methylcel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 70 publications
3
7
0
Order By: Relevance
“…The relevance of this research work spans beyond the development of novel therapeutic approaches to treat corneal injuries in horses, being also of great interest for the application in humans. In this regard, our results complement previous studies demonstrating the beneficial role of EVs in treating human corneal injuries [64,109,110], providing valuable insights for the advancement of this field.…”
Section: Discussionsupporting
confidence: 85%
“…The relevance of this research work spans beyond the development of novel therapeutic approaches to treat corneal injuries in horses, being also of great interest for the application in humans. In this regard, our results complement previous studies demonstrating the beneficial role of EVs in treating human corneal injuries [64,109,110], providing valuable insights for the advancement of this field.…”
Section: Discussionsupporting
confidence: 85%
“…The effect of BM-MSC-EVs on corneal epithelial repair was evaluated through in vitro wound healing assay [20,27,28]. HCECs were cultured in 12 well plates until 100% confluency.…”
Section: In Vitro Wound Healing Assaymentioning
confidence: 99%
“…The trait of secretory, immunomodulatory, and homing properties of these cells contributes to the function of supporting immune cells, building immune memory and immunoregulatory properties as well as antimicrobial activity (126-128). Mesenchymal stromal cells can regulate innate and adaptive immune responses via inflammatory cytokines released into the microenvironment (129). Lin et al reported for the first time that when mesenchymal stromal cells were repeatedly exposed to lipopolysaccharide (LPS) in mice, the activation of NF-kB was increased significantly, enhancing the anti-inflammatory effect of macrophages, and this process was associated with histone methylation (130).…”
Section: Trained Immunity Of Cells May Be Associated With Psoriasismentioning
confidence: 99%
“…The trait of secretory, immunomodulatory, and homing properties of these cells contributes to the function of supporting immune cells, building immune memory and immunoregulatory properties as well as antimicrobial activity ( 126 128 ). Mesenchymal stromal cells can regulate innate and adaptive immune responses via inflammatory cytokines released into the microenvironment ( 129 ). Lin et al.…”
Section: Trained Immunity Of Cells May Be Associated With Psoriasismentioning
confidence: 99%